Adsorption Behavior of Light Naphtha Components on Zeolite (5A) and Activated Carbon - Hammadi, Ahmed Najeeb; K. Shakir, Ibtehal (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
Light naphtha one of the products from distillation column in oil refineries used as feedstock for gasoline production. The major constituents of light naphtha are (Normal Paraffin, Isoparaffin, Naphthene, and Aromatic). In this paper, we used zeolite (5A) with uniform pores size (5Aº) to separate normal paraffin from light naphtha, due to suitable pore size for this process and compare the behavior of adsorption with activated carbon which has a wide range of pores size (micropores and mesopores) and high surface area. The process is done in a continuous system - Fixed bed reactor- at the vapor phase with the constant conditions of flow rate 5 ml/min, temperature 180oC, pressure 1.6 bar and 100-gram weight of each adsorbents. We notice that the molecular sieve (5A) separated the normal paraffin (C4 – C8) from light naphtha feed until equilibrium (saturation). Activated carbon separated naphthene and aromatics, in addition, the other component of normal paraffin C6 (n-hexane), C7 (n-heptane) and C8 (n-octane). And there is increasing in weight percentage of C4 (n-butane), C5 (n-pentane) and the weight percentage of isoparaffin until equilibrium (Saturation). The study showed the difference in physical adsorption behavior and the effect of pore size on these processes.